Alcohol Use Disorders: Translational Utility of DSM-IV Liabilities to the DSM-5 System. (March 2015) - Kiselica, Andrew M.; Cohn, Amy M.; Hagman, Brett T.
Abstract : Objectives: Young adults have some of the highest rates of problem drinking and alcohol use disorders (AUDs) relative to any other age. However, recent evidence suggests that the DSM-IV hierarchical classification system of AUDs does not validly represent symptoms in the population; instead, it evinces a unitary, dimensional classification scheme. The DSM-5 has been altered to fit this changing, evidence-based conceptualization. Nevertheless, little is understood about the degree to which known risk factors for DSM-IV AUD diagnoses will transfer to the new DSM-5 guidelines in this group of high-risk drinkers. The current study built a coherent model of liabilities for DSM-IV AUDs in young adults and tested for transferability to DSM-5. Methods: College students (N=496) (51.10% male) were assessed on a variety of factors related to AUD risk, including demographics, substance use (past 90 d), and drinking motives. Liability models were created using all variables in Structural Equation Modeling to test direct and indirect effects on DSM diagnostic status. The best model under the DSM-IV was chosen based on fit and parsimony. This model was then applied to the DSM-5 system to test for transferability. Results: The best fitting model for DSM-IV included direct influences of drug use, quantity-frequency of alcohol consumption, and social and coping drinking motives. Improved model fit was found when the DSM-5 system was the outcome. Conclusions: Knowledge of risk factors for AUDs seem to transfer well to the new diagnostic system.